Exploratory study on internal recycling of crude glycerol for biodiesel production: Catalyst replacement - Joana M. Dias (2016)
The present study evaluated the recycling of crude glycerol as source of catalyst for biodiesel production. For that purpose, two sets of experiments were conducted. In the first set A, biodiesel was synthesized by conventional methanolysis of sunflower oil using NaOH as catalyst at 65 degrees C during 1 h and varying catalyst concentration (0.4-1.2 wt%) or methanol to oil mole ratio (6:1-12:1). The second set (B) was performed by replicating the conditions of set A and considering the use of crude glycerol as source of catalyst. The evaluation of excess methanol and catalyst distribution in the crude products was performed. For both sets of experiments, product yield and quality (viscosity and purity) were determined. Methanol was predominantly in the glycerol phase (54-68%), with negligible effect of variation in catalyst concentration and higher percentages found when higher methanol to oil mole ratios were used, due to a higher polarity of this phase. In most cases, catalyst was predominantly in the crude glycerol (53 wt. % in average) and no clear relation was found between catalyst distribution and the different reaction conditions studied. The results from set A showed a clear influence of catalyst concentration in biodiesel conversion and a minor effect of methanol to oil molar ratio. The best conditions were 6:1 methanol to oil mole ratio and 0.6 wt. % of catalyst leading to a product yield of 95.1 wt. %, a purity of 99.3% and a viscosity of 4.59 ma The second set of experiments, B, showed different trends and variability compared to the first one, and the results indicated that catalyst might be altered during glycerol storage. It was found that the methanol to oil mole ratio affected the reaction conversion, with the highest purity (96.9 wt. %) being obtained when the highest mole ratio was used (12:1), possibly due to the reduced mass transfer limitations. Overall, the results clearly show the potential of using crude glycerol as source of catalyst, avoiding the use of new catalyst and allowing a more sustainable biodiesel production.